2004
DOI: 10.1097/00005537-200410000-00024
|View full text |Cite
|
Sign up to set email alerts
|

OK‐432 Therapy for Cervical Lymphangioma

Abstract: Intralesional injection of OK-432 is an effective treatment modality for macrocystic-type lymphangiomas in the head and neck region. It has no complications, and surgical excision in case of failure is not compromised by fibrosis. Sclerosing of macrocystic-type lymphangiomas with OK-432 should therefore be considered before surgical excision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
1
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 16 publications
3
54
1
7
Order By: Relevance
“…Previous reports have stated that surgical 86 Motz et al, OK432 Versus Doxycycline for Lymphatic Malformations excision is not more complicated after OK432 sclerotherapy. 2,3,[22][23][24]27,28 We found this to be true in the excision of an organized hematoma.…”
mentioning
confidence: 67%
“…Previous reports have stated that surgical 86 Motz et al, OK432 Versus Doxycycline for Lymphatic Malformations excision is not more complicated after OK432 sclerotherapy. 2,3,[22][23][24]27,28 We found this to be true in the excision of an organized hematoma.…”
mentioning
confidence: 67%
“…[12][13][14][15] However, several authors have suggested that sclerotherapy may be a more appropriate first-line therapy. 16,17 Although sclerotherapy is now well established in the treatment of neonatal and paediatric cystic hygromas, there have been relatively few cases reported of its use in adult patients. Some success has been reported in small numbers of adults with sclerotherapy agents such as OK-432.…”
Section: Discussionmentioning
confidence: 99%
“…[11] The centripetal theory discusses aberrant congenital lymphatic development. [12] The end result for both theories is the inability of the peripheral lymphatics to drain into the jugular sacs. In adults, lymphangiomas may occur from delayed proliferation of cell rests, either spontaneously or in response to infection or trauma.…”
Section: Discussionmentioning
confidence: 99%